ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENGGUNAAN INTERNET BANKING DI BANJARMASIN - Muthia - Harnida (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2014)
ABSTRACT This study is to investigate the factors which affect the use of internet banking in Indonesia especially in Banjarmasin. The survey used 80 respondents including the employees, executives, university students, and others. The data analyzed is only 52 respondents. The factors tested in this research includes the attitudes which proxies by 5 attributes, namely relative superiority, conformity, complexity, friability, and risk. The others factors are subjective norms or social factors, and controlling of behavior which proxies by efficacy and the support of government and technology. The research analysis used linear multiple regression, and the result indicates that the factors of attitude including relative superiority, conformity, and friability have the effect on using the internet banking while the subjective norms and controlling of behavior have no effects on using the internet banking. Keywords: Internet banking, attitudes, social factor, controlling, behavior, effect.